2016
DOI: 10.4067/s0718-381x2016000100003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Profile and Characterization of Oral and Maxillofacial injuries in Women Victims of Interpersonal Violence

Abstract: ABSTRACT:The objective of this study was to determine the epidemiological profile of women victims of violence and characterize the injuries affecting their maxillofacial region. This was an analytic study using secondary data from 470 expert reports of domestic violence involving women, collected from January 2007 to December 2011 in the Department of Dentistry of the Institute of Legal Medicine in the city of Feira de Santana, Bahia, Brazil. The majority of the examined women were Afro-caucasian (72.6 %), si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 12 publications
2
11
0
5
Order By: Relevance
“…In cases where physical aggression was the etiological agent, domestic violence was the most prevalent; we can infer that women were the main victims and their companion, the aggressor. This finding is consistent with data reported in other studies that show that when there is a prevalence of violence against women, it is generally practiced by men, either the victim’s husband, boyfriend, or intimate partner ( 10 , 16 , 22 , 23 ). The aggressors use physical force, with punches and kicks (the hands and feet are considered blunt instruments) ( 10 , 23 ).…”
Section: Discussionsupporting
confidence: 92%
“…In cases where physical aggression was the etiological agent, domestic violence was the most prevalent; we can infer that women were the main victims and their companion, the aggressor. This finding is consistent with data reported in other studies that show that when there is a prevalence of violence against women, it is generally practiced by men, either the victim’s husband, boyfriend, or intimate partner ( 10 , 16 , 22 , 23 ). The aggressors use physical force, with punches and kicks (the hands and feet are considered blunt instruments) ( 10 , 23 ).…”
Section: Discussionsupporting
confidence: 92%
“…30 A study by Saddki et al 10 found that bruises, abrasions, and lacerations were the most prevalent type of maxillofacial injuries, and the middle third of the face was the most affected region. 30 A study by Saddki et al 10 found that bruises, abrasions, and lacerations were the most prevalent type of maxillofacial injuries, and the middle third of the face was the most affected region.…”
Section: Discussionmentioning
confidence: 99%
“…Another study performed in Brazil based on forensic data reported that the most prevalent lesions among women victims of domestic violence were edema, fracture, tooth luxation, and bruising. 30 A study by Saddki et al 10 found that bruises, abrasions, and lacerations were the most prevalent type of maxillofacial injuries, and the middle third of the face was the most affected region. It is important to emphasize that although these patterns suggest minor trauma, these injuries need attention because they may affect the victim's self-esteem and generate intense emotional and social suffering.…”
Section: Discussionmentioning
confidence: 99%
“…The information obtained in the present study agrees with several studies that conclude that the aggressor is usually the husband or partner of the assaulted woman. 13,22,25,26 Among the limitations of the present study is the short period evaluated due to the availability of expert reports. In addition, secondary data were used, so it was not possible to analyze aspects other than those included in the reports, such as the geographical location where the aggression occurred, the presence of witnesses, the consumption of alcohol or psychoactive substances, the evolution of injuries, and the mechanisms of aggression.…”
Section: Discussionmentioning
confidence: 97%
“…21 In Brazil, da Silva et al assessed 223 women victims of violence, finding out that 197 of them had intraoral injuries, with 51% of these reporting injuries in teeth. 22 Several studies have found that the most common mechanism for producing maxillofacial injuries is fist blowing; usually, a heavy blow causes the woman to fall to the floor, so that no fractures occur unless the woman is victim of several blows. 14,23 In the present study, it was not possible to identify the mechanism that caused the lesion since the Protocol for Expert Reporting did not contain this item specifically.…”
Section: Discussionmentioning
confidence: 99%